WHERE AND HOW DID THE RUPTURES OF DECEMBER 26, 2004 AND MARCH 28, 2005 EARTHQUAKES NEAR SUMATRA ORIGINATE? - Mukhamediev Sh.A.; Galybin A.N. (My University, 2006)
The earthquakes of December 26, 2004, (magnitude Mw = 9.3; epicenter coordinates 3.3° N, 96.0° E; depth h ≈ 30 km [1, 2]; approximately 300 000 victims due to the tsunami on the Indian Ocean coast) and March 28, 2005, (Mw = 8.6; 2.1° N, 97.0° E; h ≈ 30 km; more than 1000 victims), which occurred in the Sunda Trench west of Sumatra Island, confirm the common opinion that the search for factors controlling the origin of great earthquakes in island arcs is a problem of vital importance in seismology.